Can positive faith-based encounters influence Australian young people's drinking behaviours?. (June 2017) - Hutton, Alison; Whitehead, Dean; Ullah, Shahid
Purpose: Alcohol-related accidents and injuries occur disproportionately within young people – especially when gathering at social events. This study represents a partnership between a faith-based group of volunteers specifically trained to counsel and support young people to reduce their risk of alcohol-related harm, Adelaide City Council, and the South Australian Police Force aimed at reducing risk-related alcohol consumption in a metropolitan nightclub district area. It posits that supporting young people to party safely, alongside positive community engagement, may deter unsafe consumption practices – such as pre-loading and binge-drinking. Methods: Retrospective online survey evaluated the impact on attitudes of young people who received the intervention. Results: Findings suggest volunteers were perceived as positive role models who demonstrated a genuine sense of care and ability to support. As a result, one-third of respondents identified potentially more carefully pre-plan their drinking behaviour on their next night out. Conclusion: This study demonstrates that young people are responsive to positive interventions and that future pre-planning may become a more natural part of their party routine – resulting in less likelihood of alcohol-related risk. The outcome measure, that young people's intentions to moderate their drinking as a result of positive encounters, is an important one.